p16 as an independent marker for detection of high-risk HPV in oral submucous fibrosis and oral squamous cell carcinoma - Archana Sudhakaran; Kaveri Hallikeri; Biji Babu (Wolters Kluwer Medknow Publications, 2019)
Background: An alarming increase in incidence of high-risk human papillomavirus (HPV) positive tumors in head and neck squamous cell carcinoma (HNSCC) by 25% and 70% in oropharyngeal HNSCC cannot be ignored. The early oncogenes of HPV, E6, and E7 play a key role in carcinogenesis. HPV associated tumors have a better clinical outcome and a favorable prognosis. The p16 expression has high concordance with other methods of HPV detection, ascertaining p16 as a surrogate marker for HPV. Objective: To assess the immunohistochemical expression of p16 in oral submucous fibrosis (OSF) and oral squamous cell carcinoma (OSCC) with and without coexistent OSF as a marker for high-risk HPV detection. Materials and Methods: Tissue blocks of 70 cases including normal, OSF, OSCC with and without OSF were subjected to IHC staining with a p16INK4A monoclonal antibody. (Biogenex, San Roman). The p16 expression was noted according to percent positivity and pattern. The data were tabulated, statistically analyzed using the Chi-square test and the P value was assessed. Results: The percentage of p16 positive cells raised from normal to OSF to OSCC with and without OSF. In addition, a shift from nuclear to cytoplasmic expression from normal to OSCC was noted with a statistical significance (P < 0.001). However, no statistical significance was established with any clinicopathologic parameters except age (P = 0.012) and habits (P= 0.023). Conclusion: The presence of HPV using p16 was not detected in OSF but was positive in OSCC. Altered pattern of expression from normal to OSF to OSCC indicates promising use of p16 as a diagnostic marker.